GO-GN Special Collection: Editorial. Issue 1 (13th December 2021) - Weller, Martin
The Global OER Graduate Network (GO-GN) is a global community of researchers in Open education. For this collection we invited papers from GO-GN members (past and present) to highlight the research they are undertaking and the impact of the network. As well as conventional research papers, we encouraged joint papers with other members or external to the network; shorter, work-in-progress papers; case studies or narrative accounts of OEP and suggestions for innovative formats. The collection provides an opportunity for members to showcase their work, gain feedback and demonstrate the value of the network. The GO-GN team also offered to act as mentors on request for any authors who wished to work up their contributions.